Stakeholders Involvement in Sediment Management in Rawa Pening Lake, Central Java, Indonesia - Farhan Akmala Putra; Titik Ekowati; Forita Dyah Arianti (Postgraduate, University of Mataram, 2025)
Lake Rawapening is one of the 15 lakes prioritized for preservation based on Presidential Regulation No. 60 of 2021. due to high environmental degradation caused by sedimentation rates that can reduce water depth and quality and harm ecosystem sustainability. This research aims to analyze the roles and contributions of each stakeholder and key actor in the utilization of sediment from Lake Rawapening. The research method used in this study is a qualitative survey method. The number of respondents in this study consists of 18 key informants, 15 main informants, and 3 supporting informants. The analysis used employs Actor Network Theory analysis with the Social Network Visualizer version 3.1 application. Research shows that in the utilization of sediments in Lake Rawapening. The government as the determiner of policy formation and implementation; the sediment utilization institution, which is currently inactive, playing a role in coordination and synergy among stakeholders; sediment dredging fishermen as sediment extractors; sediment porters as the delivery service from the boat to the sediment collection site; sediment collectors as raw material distributors and managers of the sediment collection process; and fertilizer distribution as the link between producers and farmers. The actor with the highest EVC in sediment utilization at Lake Rawapening is the sediment collector at node 5, who becomes the most important actor with an EVC of 100% due to extensive involvement with various parties. Fertilizer distributors from Purwodadi and Ambarawa followed in second place with an EVC of 87.51%, while sediment porters recorded the lowest EVC (0%). The collector at node 7 has the highest CC score (43.61%). Lake Rawapening's sediment collectors have a 39.45% control rate (BC score = 39.45)